Linking Islamic work ethic to computer use ethics, job satisfaction and organisational commitment in Malaysia - Mohamed, Norshidah; Abdul Karim, Nor Shahriza; Hussein, Ramlah (Victoria University, 2010)
This research seeks to investigate whether Islamic work ethic is linked to individuals’ attitudes towards computer use ethics, job satisfaction and organisational commitment. The research used a cross-sectional self-administered survey method in the International Islamic University Malaysia. A total of 310 survey questionnaires were distributed to academic staff in four faculties i.e. Engineering, Information and Communication Technology, Human Science and Islamic Revealed Knowledge and Economics and Management Sciences faculties. Cluster sampling was used in the selection of academic staff from several randomly chosen class schedules. The study found that Islamic work ethic within a university environment is linked to individuals’ attitudes towards computer use ethics, job satisfaction and organisational commitment. Implications and areas for future research are also discussed.